Text linguistics and Skopos theory and their application in translation teaching - Sugeng Hariyanto (Jurnal Linguistik Terapan, 2015)
Translation industry is developing very fast with the economic globalization and digital/internet technology development. Unfortunately, the teaching of translation in universities has not adopted techniques that can response this situation. This paper aims to propose a translation teaching technique to train the students to produce target texts demanded in the translation business. The technique is proposed by considering two influential concepts in translation theory, i.e., Text Linguistics and Skopos Theory. Text linguistics is a branch of linguistics that deals with texts as communication systems. Text linguistics takes into account the form of a text and its setting, i.e. the way in which it is situated in an interactional, communicative context. In relation to translation, it can be said that translation is not only the business of analyzing the source text sentence by sentence. Instead, the author and the intended audience and the purpose of communication should also be considered. Skopos theory is closely related to text-types and also emphasizes the importance of translation purposes. With these ideas as the basis, this article gives example how to apply text linguistics and skopos theory in classroom context to teach functional text translation. The translation teaching materials are selected based on the text type and difficulty levels, students are trained to do text-analysis and be made aware of the purpose of the source text is not always the same with the purpose of the target text. Prior to giving a translation practice, therefore, the teacher writes the clearest translation brief possible.